Morphological, Chemical, and Thermal Characteristics of Nanofibrillated Cellulose Isolated Using Chemo-mechanical Methods - Solikhin, Achmad; Hadi, Yusuf Sudo; Massijaya, Muh Yusram; Nikmatin, Siti (Makara Journal of Science, 2019)
The objective of this research was to analyze the morphology, crystallinity, elemental components, and functional group changes, as well as thermal stability of nanofibrillated cellulose (NFC). Nanofibrillated cellulose has an irregular and aggregated shape with a diameter of about 100 nm. NFC self-aggregations were observed due to hydrogen bonding and Van-der Waals forces. The cellulose crystallinity index, atomic size, and polymorph of the NFC sample were found to be 63.57%, 2.2 nm, and cellulose I, respectively. The NFC sample was composed of various elemental components, such as C, O, N, Na, Al, Si, and K. IR analysis showed only small amounts of hemicellulose and lignin deposits, whereas cellulose functional groups appeared inseveral wavenumbers. Aromatic and oxygenated compounds, such as carboxylic acids, phenols, ketones, and aldehydes, were deposited as extractive on NFC; these compounds were associated with cellulose, hemicellulose, and lignin. The NFC thermal degradationprocess consisted of four steps: water evaporation (50-90 °C); hemicellulose degradation and glycosidic linkage cleavage (250-325 °C); amorphouscellulose and lignin degradation (325-429.29 ºC); and cellulose crystalline degradation (above 429.29 °C).